THE USE OF ORIGINAL VIDEO MATERIALS FOR THE STRUCTURE OF PROJECT ACTIVITY SKILLS IN FOREIGN LANGUAGE LESSONS IN SCHOOLS - Mahamadiyeva Muhlisa Abdurashid qizi; Mamatqodirova Gulnigor (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The article discusses the possibility of using authentic video materials for the formation of project activity skills in English lessons in schools. The classification and requirements for the method of projects are revealed.